Pelatihan Penggunaan Aplikasi Canva dalam Optimalisasi Bahan Ajar bagi Guru PAUD di Wilayah Ibu Kota Nusantara - Putri, Ayu Aprilia Pangestu; Wahyuningsih, Tri; Setiawan, Ady; Fauzi, Chandra; Cahyaningrum, Gyta Krisdiana; Winanti, Suci; Adisty, Deshiva Idfi Aji (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Early Childhood Education Teachers need a variety of learning strategy applications, which aims to improve the quality of learning that is appropriate for early childhood education. In learning activities, the use of Artificial Intelligence-based technology such as Canva is one alternative strategy to help teachers compile interesting and visual teaching materials for early childhood. This community service activity aims to provide training to early childhood education teachers in Muara Jawa District, the Indonesian Capital Region, in utilizing the Canva application to create appropriate teaching materials and apply learning strategies that are appropriate to the needs of early childhood. The method used includes three stages, namely the initial stage, the implementation stage and the stage. The results of the activity showed the enthusiasm and active involvement of teachers while receiving the Canva Application material. Teachers were also able to produce creative and interesting visual teaching materials, which can be used directly in the learning process. This activity shows that the use of Canva can improve teacher competence in designing teaching materials while enriching children's learning experiences through more enjoyable and communicative media.